Identification of the water-gap in Albizia julibrissim (Fabaceae: Mimosoideae) following wet and dry heat. (3rd July 2020) - Yang, Yashu; Jaganathan, Ganesh K.; Biddick, Matthew; Li, Jiajin; Liu, Baolin
Abstract: Although physical dormancy (PY) has been noted in Albizia julibrissim Durazz. seeds, the conditions that facilitate dormancy break, remain poorly understood. In the present study, we asked (1) what conditions are required to break dormancy and (2) whether these structures differ between dormancy-breaking methods. Imbibition tests demonstrated that the seed coat is impermeable to water, confirming that seeds exhibit PY. Seeds dipped in hot water for 30 sec broke dormancy by forming circular lid-like opening at the lens (i.e. water-gap Type-II) and germinated readily (over 90% in both light and darkness). However, seeds subjected to dry heat treatments of 80, 100 and 150 °C for 1 and 5 min revealed that temperature and treatment duration are key determinants of dormancy break. Seeds that experienced lower temperatures for a short duration remained dormant, whereas seeds exposed to higher temperature for longer durations were entirely inviable. Unlike wet heat treatment, dry heat pulled the lens cells apart, resulting in a non-circular, lid-like opening, a form of the lens opening not yet documented in Mimosoideae.